Estratégias de aprendizagem e desempenho oral: estudo de caso
Language Learning Strategies and Oral Performance: A Case Study. This article presents the results of a quantitative analysis on the link between (1) the use of language learning strategies (LLS) and (2) the oral performance among beginner students of the Portuguese for Foreigners Course at University of Porto, in the 2014-2015 academic year. The findings are: there is a positive correlation, but not significant, between (1) and (2), and students with the best results in the oral assessment have higher means in the LLS use, use more LLS in high frequency level and over-perform on the use of specific LLS.